Alkenone concentration and accumulation rate in sediment of ODP Hole 104-642B - Bachem, Paul E; Risebrobakken, Bjørg; McClymont, Erin L (Supplement to: Bachem, PE et al. (in prep.): Export productivity in the Pliocene Norwegian Sea., 2016)
To be submitted by the author.